Salinity effects on water potential and the normalized difference vegetation index in four species of a saline semi-arid ecosystem - Hebert Hernán Soto Gonzáles; Ofelda Peñuelas-Rubio; Leandris Argentel-Martínez; Aurelio Leyva Ponce; María Hermelinda Herrera Andrade; Mirza Hasanuzzaman; Jorge González Aguilera; Paulo Eduardo Teodoro (PeerJ, 2021)
This study was carried out during January 2020–December 2020 in a semi-desert ecosystem in southern Sonora, Mexico, to determine the annual and daily variations in water potential and the normalized difference vegetation index (NDVI) of Bursera fagaroides Engl., Monogr. Phan., Parkinsonia aculeata L., Sp. Pl.; Prosopis laevigata (Humb. & Bonpl. ex Willd.), and Atriplex canescens (Pursh) Nutt. Soil electrical conductivity, cation content, and physical characteristics were determined at two depths, and water potential (ψ) was measured in roots, stems, and leaves. The daily leaf ψ was measured every 15 days each month to determine the duration of stress (hours) and the stress intensity (SI). The electrical conductivity determinations classified the soil in the experimental area as strongly saline. A significant difference was noted in electrical conductivity between soil depths. The four studied species showed significant gradients of ψ in their organs. In this soil, all four species remained in a stressed condition for approximately 11 h per day. The mean SI was 27%, and B. fagaroides Engl., Monogr. Phan. showed the lowest value. The four species showed increased NDVI values during the rainy months, with P. laevigata (Humb. & Bonpl. ex Willd.) and Parkinsonia aculeata L., Sp. Pl. showing the highest values. The capacity for ψ decrease under saline conditions identified A. canescens (Pursh) Nutt., B. fagaroides Engl., Monogr. Phan. and P. aculeata L., Sp. Pl. as practical and feasible alternatives for establishment in saline soils in southern Sonora for purposes of soil recovery and reforestation.